A semi-decentralized control architecture for high-mix-low-volume factories in Industry 4.0. (October 2021) - Didden, Jeroen B.H.C.; Dang, Quang-Vinh; Adan, Ivo J.B.F.
Abstract: Industry 4.0 introduces a shift towards a more decentralized planning and control architecture in order to combat the changing production environment. Hence, this paper presents a semi-decentralized control architecture for the high-mix-low-volume industry to improve production planning and control. The proposed architecture consists of three components: the ERP system, a global control unit, and shop floor planning. The system's performance is improved through better use of knowledge and creation of virtual manufacturing cells on the shop floor, allowing for better control in case of uncertainties or changes within product mix and volume.